A high-performance thermal battery composite positive electrode material and preparation method thereof

By preparing high-performance composite positive electrode materials by combining nickel chloride with composite molten salt electrolyte, magnesium oxide and titanium nitride ball mill, the high resistivity and melt-impregnation leakage problems of hot battery positive electrode materials are solved, and the high current discharge performance and voltage platform are improved stability.

CN114388756BActive Publication Date: 2025-01-14WUHAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111607595.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-27
Publication Date
2025-01-14
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

Existing hot battery positive electrode materials such as iron disulfide and oxide materials have high resistivity, easy decomposition and matching with electrolytes, which limits their application range. It is difficult for chloride positive electrode materials to improve their performance due to high resistivity and melt-impregnation leakage.

Method used

Using nickel chloride as the active substance, high-performance composite positive electrode materials are prepared by ball milling with composite molten salt electrolyte and additives such as magnesium oxide and titanium nitride. Combining the adsorption properties of magnesium oxide and the conductivity of titanium nitride, avoiding melt-impregnation and leakage. Reduce battery internal resistance.

Benefits of technology

It improves the high current discharge performance and voltage platform stability of the positive electrode material, reduces the internal resistance of the battery, improves the specific discharge capacity and voltage platform, and solves the problems of high resistivity and melt-impregnation leakage of nickel chloride materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114388756B_ABST
    Figure CN114388756B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-performance thermal battery composite positive electrode material and a preparation method thereof, wherein the high-performance thermal battery composite positive electrode material is obtained by mixing and ball-milling nickel chloride and composite molten salt electrolyte powder, wherein the mass fraction of nickel chloride is 60-90%, and the mass fraction of composite molten salt electrolyte powder is 10-40%. The positive electrode material obtained by mixing and ball-milling nickel chloride and composite molten salt electrolyte powder in the present invention maintains a high active material ratio, has excellent large current discharge performance, and has a stable voltage platform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrodes composed of or including active materials, and in particular relates to a high-performance thermal battery composite positive electrode material and a preparation method thereof. Background Art

[0002] Thermal batteries have a wide range of applications due to their various advantages, such as rapid activation, long storage time, large output current, and adaptability to harsh environments. With the rapid development of industrialization, traditional thermal batteries (such as Li / FeS2) are difficult to meet the performance requirements of electronic information equipment upgrades, so it is necessary to further develop existing thermal battery systems and explore new thermal battery systems to improve thermal battery performance.

[0003] At present, the more mature positive electrode materials include sulfide systems based on iron disulfide and oxide systems based on vanadium oxide (LVO), but due to some defects of the materials themselves, they are limited in application. For example, the high resistivity and easy decomposition of iron disulfide limit its applicable temperature range, and the matching problem between oxide materials and electrolytes is also a major obstacle to its application. Compared with traditional positive electrode materials, chloride positive electrode materials have the characteristics of higher theoretical voltage, suitable for large current discharge and high decomposition temperature, and are the current research focus in the field of thermal battery positive electrode materials. However, the high resistivity of chloride positive electrode materials such as nickel chloride and the phenomenon of easy melting and leakage with electrolyte limit their further development and application. A common method to improve the positive electrode leakage defect is to add additives such as MgO, Al2O3, SiO2 to the positive electrode, and use the bonding properties of the additive powder to inhibit leakage. However, this method often leads to a decrease in the content of active materials in the positive electrode due to the introduction of too much insulating binder, which increases the internal resistance of the battery and reduces the overall discharge performance of the battery. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a high-performance thermal battery composite positive electrode material using nickel chloride as an active material and a preparation method thereof in view of the above-mentioned deficiencies in the prior art.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] Provided is a high-performance thermal battery composite positive electrode material, which is obtained by mixing and ball-milling nickel chloride and composite molten salt electrolyte powder, wherein the mass fraction of nickel chloride is 60-90%, and the mass fraction of composite molten salt electrolyte powder is 10-40%.

[0007] According to the above scheme, the preparation method of nickel chloride is as follows: NiCl2·6H2O is placed in a vacuum drying oven, dried at 200°C for 2-4h, ground after cooling and taking out, and then transferred to a tubular furnace, heated from room temperature to 250-350°C at a heating rate of 10°C / min, kept warm for 2-4h, then heated to 500-700°C, kept warm for 4-6h, and pure NiCl2 powder is obtained. The NiCl2 material prepared according to the above scheme is loose, and the microstructure is 20-40μm flakes with a thickness of about 2μm. The loose flake structure is conducive to the uniform mixing of the positive electrode material, which has a certain promoting effect on improving the discharge performance of the battery.

[0008] According to the above scheme, the composite molten salt electrolyte powder is obtained by mixing molten salt electrolyte powder and additives and ball milling for 1 to 2 hours, wherein the mass fraction of molten salt electrolyte powder is 30 to 70%, and the mass fraction of additives is 30 to 70%. Preferably, the mass ratio of molten salt electrolyte powder to additives is 1:1.

[0009] According to the above scheme, the molten salt electrolyte powder is one of LiCl-KCl molten salt powder, LiCl-LiF-LiBr molten salt powder, and LiF-LiBr-KBr molten salt powder, preferably LiCl-LiF-LiBr molten salt powder. Under an argon atmosphere, the raw material powder for preparing the molten salt electrolyte powder is placed in a ball mill for ball milling, and then the ball-milled mixed powder is pre-melted to obtain molten salt, and then the molten salt is crushed and ball milled at a speed of 300-400 rpm for 2-3 hours to obtain a molten salt electrolyte powder.

[0010] According to the above scheme, the pre-melting treatment process conditions are: pre-melting under the protection of argon atmosphere, the pre-melting temperature is 100-150°C higher than the low eutectic temperature of the raw material powder, the pre-melting time is 4-6h, and finally cooling to room temperature with the furnace.

[0011] According to the above scheme, the additive is a mixed powder obtained by ball milling magnesium oxide and titanium nitride, wherein the mass fraction of magnesium oxide is 0-90%, and the mass fraction of titanium nitride is 10-100%. The preferred mass ratio of magnesium oxide to titanium nitride is one of 0:10, 3:7, 5:5, and 7:3. As additives for positive electrode materials, magnesium oxide and titanium nitride have excellent adsorption properties that can prevent the nickel chloride material from leaking during the operation of the thermal battery. At the same time, the electrical conductivity of the titanium nitride material improves the electronic conductivity of the positive electrode material, reduces the internal resistance of the battery, and improves the discharge performance of the battery.

[0012] The present invention also provides a method for preparing the high-performance thermal battery composite positive electrode material, the specific steps of which are as follows:

[0013] 1) Weigh nickel chloride and composite molten salt electrolyte powder in proportion and set aside;

[0014] 2) The nickel chloride and composite molten salt electrolyte powders weighed in step 1) are mixed and ball-milled to obtain a high-performance thermal battery composite positive electrode material.

[0015] According to the above scheme, the ball milling process conditions in step 2) are: ball milling speed 200-350 rpm, ball milling time 1-2 h.

[0016] The present invention also includes the application of the high-performance thermal battery composite positive electrode material as a positive electrode material in the field of thermal batteries.

[0017] The present invention is based on the fact that the positive electrode material of the thermal battery contains molten salt electrolyte powder. A composite additive is obtained by adding NiCl2, magnesium oxide and titanium nitride to the mixed ball mill. The composite additive combines the adsorption effect of magnesium oxide on the electrolyte and the excellent conductivity of titanium nitride, avoids the defect of increasing the internal resistance due to the addition of insulating additives (such as magnesium oxide), improves the discharge specific capacity and voltage platform of the battery without changing the content of active substances in the positive electrode, and provides a new solution to the problems of melt leakage during the discharge of the NiCl2 positive electrode and the high resistivity of the NiCl2 material itself.

[0018] The beneficial effects of the present invention are as follows: 1. The positive electrode material obtained by mixing nickel chloride and composite molten salt electrolyte powders and ball milling maintains a relatively high active material ratio, has excellent large current discharge performance, and has a stable voltage platform. 2. The preparation method of the present invention is simple in process and low in cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The thermal battery assembled when the additive in the positive electrode material of Example 1 of the present invention is titanium nitride and the comparative sample at 500°C and 0.2A / cm 2 Discharge curve under conditions;

[0020] Figure 2 This is a SEM image of the composite positive electrode material prepared in Example 1;

[0021] Figure 3 The thermal battery assembled for Example 1 was heated at 500°C and 0.1A / cm 2 SEM and EDS images of the single cell stack after discharge under the following conditions;

[0022] Figure 4 The thermal battery assembled in Example 2 when the ratio of magnesium oxide to titanium nitride in the positive electrode material additive is 3:7 is subjected to a load of 500°C and 0.1A / cm 2 Discharge curve under conditions;

[0023] Figure 5 The thermal battery assembled when the positive electrode material additives in Example 3 are magnesium oxide:titanium nitride = 5:5 is at 500°C and 0.3A / cm 2Discharge curve under conditions;

[0024] Figure 6 The thermal battery assembled when the positive electrode material additives in Example 4 are magnesium oxide: titanium nitride = 5:5, nickel chloride: composite molten salt electrolyte powder = 7:3 is at 500°C and 0.1A / cm 2 Discharge curve under . DETAILED DESCRIPTION

[0025] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0026] The raw materials and reagents used in the examples of the present invention are all analytically pure, wherein the particle size of the titanium nitride powder used is 3-10 μm. The ball milling process conditions in the examples of the present invention are ball milled at 300 rpm for 1 hour if no description is given.

[0027] Example 1

[0028] A high-performance thermal battery composite positive electrode material, the preparation method of which is as follows:

[0029] 1) In an argon atmosphere, LiCl powder, LiF powder and LiBr powder are placed in a ball mill at a mass ratio of 22:9.6:68.4, and then the ball-milled mixed powder is pre-melted to obtain LiCl-LiF-LiBr molten salt, and then the molten salt is crushed and ball-milled at a speed of 300-400 rpm for 2 hours to obtain a molten salt electrolyte powder, and finally the molten salt electrolyte powder and the additive titanium nitride powder are weighed at a mass ratio of 1:1, and ball-milled for 1 hour to obtain a composite molten salt electrolyte powder;

[0030] 2) NiCl2·6H2O was placed in a vacuum drying oven and vacuum dried at 200°C for 4 hours. After natural cooling, it was ground evenly and transferred to a tube furnace. The temperature was increased from room temperature to 300°C at a heating rate of 10°C / min and kept for 2 hours. Then, the temperature was increased to 600°C and kept for 4 hours to obtain pure NiCl2 powder.

[0031] 3) The composite molten salt electrolyte powder prepared in step 1) and the NiCl2 powder prepared in step 2) are weighed in a mass ratio of NiCl2 powder: composite molten salt electrolyte powder = 8:2, and then ball-milled and mixed at 300 rpm for 1 hour to obtain a composite positive electrode material.

[0032] Under argon atmosphere, the composite positive electrode powder (0.2 g) obtained in this example was spread in a stainless steel tableting mold with an inner diameter of 17.5 mm, and then 0.3 g of electrolyte separator powder (LiCl-LiF-LiBr-MgO) was spread on it, and the tablet was pressed at a pressure of 5 MPa, and the pressure was maintained for 1 min. The positive electrode / electrolyte separator composite sheet was obtained by demolding. A lithium-boron alloy sheet was further selected as the negative electrode material, and assembled with the positive electrode / electrolyte separator composite sheet to obtain a thermal battery monomer.

[0033] In an argon environment and with an external heat source temperature of 500°C, the thermal battery discharge current density was measured to be 0.2A / cm 2 , the discharge curve test results when the cut-off voltage is 0.3V are as follows Figure 1 As shown by the solid line in the middle, its discharge specific capacity can reach 373.75mAh / g, the discharge voltage platform is stable, the maximum voltage during the discharge process can reach 2.38V, and the corresponding maximum specific power is 7.15kW / Kg.

[0034] The titanium nitride powder additive in this embodiment is replaced with magnesium oxide powder of the same mass, and the composite positive electrode material is prepared by the same method as in this embodiment and then assembled into a thermal battery cell as a comparison sample of this embodiment. The discharge curve is tested under the same conditions. The test results are as follows: Figure 1 As shown by the dotted line, the discharge voltage platform is stable, the maximum voltage during the discharge process reaches 2.26V, and the corresponding maximum specific power is 6.79kW / Kg. Compared with the composite positive electrode material of this embodiment, although the composite positive electrode material has a slightly higher specific capacity, its operating voltage is lower and the specific power is smaller.

[0035] Figure 2 This is a SEM picture of the composite positive electrode material prepared in this example. From the picture, it can be seen that the molten salt electrolyte and irregularly shaped titanium nitride powder are evenly distributed around the flaky nickel chloride.

[0036] Figure 3 The thermal battery prepared for this example was heated at 500°C and 0.1A / cm 2 The SEM and EDS images of the single cell stack after discharge under high temperature conditions show that the positive electrode, electrolyte layer and negative electrode in the stack after high temperature discharge are clearly stratified, and no obvious leakage is found. The EDS element distribution diagram shows that titanium nitride as a positive electrode additive can better maintain the morphology of the positive electrode during the discharge process, and there is no diffusion or leakage of the positive electrode material to the electrolyte layer.

[0037] Example 2

[0038] A high-performance thermal battery composite positive electrode material, the preparation method of which is as follows:

[0039] 1) The dried magnesium oxide and titanium nitride are fully ball-milled in a mass ratio of 3:7 to obtain an additive powder, and LiCl powder, LiF powder, and LiBr powder are placed in a ball mill in an argon atmosphere in a mass ratio of 22:9.6:68.4, and then the ball-milled mixed powder is pre-melted to obtain LiCl-LiF-LiBr molten salt, and then the molten salt is crushed and ball-milled at a speed of 300-400 rpm for 2 hours to obtain a molten salt electrolyte powder, and finally the molten salt electrolyte powder and the additive powder are weighed in a mass ratio of 1:1, and ball-milled for 1 hour to obtain a composite molten salt electrolyte powder;

[0040] 2) NiCl2·6H2O was placed in a vacuum drying oven and vacuum dried at 200°C for 4 hours. After natural cooling, it was ground evenly and transferred to a tube furnace. The temperature was increased from room temperature to 300°C at a heating rate of 10°C / min and kept for 2 hours, and then increased to 600°C and kept for 4 hours to obtain pure NiCl2 powder;

[0041] 3) The composite molten salt electrolyte powder prepared in step 1) and the NiCl2 powder prepared in step 2) are weighed in a mass ratio of NiCl2 powder: composite molten salt electrolyte powder = 8:2, and then ball-milled to obtain a composite positive electrode material.

[0042] Under argon atmosphere, the composite positive electrode powder (0.2 g) obtained in this example was spread in a stainless steel tableting mold with an inner diameter of 17.5 mm, and then 0.3 g of electrolyte separator powder (LiCl-LiF-LiBr-MgO) was spread on it, and the tablet was pressed at a pressure of 5 MPa, and the pressure was maintained for 1 min. The positive electrode / electrolyte separator composite sheet was obtained by demolding. A lithium-boron alloy sheet was further selected as the negative electrode material, and assembled with the positive electrode / electrolyte separator composite sheet to obtain a thermal battery monomer.

[0043] In an argon environment and with an external heat source temperature of 500°C, the thermal battery discharge current density was measured to be 0.1A / cm 2 , the discharge curve test results when the cut-off voltage is 0.3V are as follows Figure 4 As shown by the solid line in the middle, its discharge specific capacity can reach 285.63mAh / g, the discharge voltage platform is stable, the maximum voltage during the discharge process can reach 2.47V, and the corresponding maximum specific power is 3.71kW / Kg.

[0044] The titanium nitride powder additive in this embodiment is replaced with magnesium oxide powder of the same mass, and the composite positive electrode material is prepared by the same method as in this embodiment and then assembled into a thermal battery cell as a comparison sample of this embodiment. The discharge curve is tested under the same conditions. The test results are as follows: Figure 4As shown by the dotted line, the discharge voltage platform is stable, the maximum voltage during the discharge process reaches 2.44V, and the corresponding maximum specific power is 3.66kW / Kg. Compared with the composite positive electrode material of this embodiment, although the composite positive electrode material has a slightly higher specific capacity, its operating voltage is lower and the specific power is smaller.

[0045] Example 3

[0046] A high-performance thermal battery composite positive electrode material, the preparation method is as follows:

[0047] 1) The dried magnesium oxide and titanium nitride are fully ball-milled in a mass ratio of 5:5 to obtain an additive powder; LiCl powder, LiF powder, and LiBr powder are placed in a ball mill in an argon atmosphere in a mass ratio of 22:9.6:68.4, and then the ball-milled mixed powder is pre-melted to obtain LiCl-LiF-LiBr molten salt, and then the molten salt is crushed and ball-milled at a speed of 300-400 rpm for 2 hours to obtain a molten salt electrolyte powder, and finally the molten salt electrolyte powder and the additive powder are weighed in a mass ratio of 1:1, and ball-milled for 1 hour to obtain a composite molten salt electrolyte powder;

[0048] 2) NiCl2·6H2O was placed in a vacuum drying oven and vacuum dried at 200°C for 4 hours. After natural cooling, it was ground evenly and transferred to a tube furnace. The temperature was increased from room temperature to 300°C at a heating rate of 10°C / min and kept for 2 hours, and then increased to 600°C and kept for 4 hours to obtain pure NiCl2 powder;

[0049] 3) The composite molten salt electrolyte powder prepared in step 1) and the NiCl2 powder prepared in step 2) are weighed in a mass ratio of NiCl2 powder: composite molten salt electrolyte powder = 8:2, and then ball-milled to obtain a composite positive electrode material.

[0050] Under argon atmosphere, the composite positive electrode powder (0.2 g) obtained in this example was spread in a stainless steel tableting mold with an inner diameter of 17.5 mm, and then 0.3 g of electrolyte separator powder (LiCl-LiF-LiBr-MgO) was spread on it, and the tablet was pressed at a pressure of 5 MPa, and the pressure was maintained for 1 min. The positive electrode / electrolyte separator composite sheet was obtained by demolding. A lithium-boron alloy sheet was further selected as the negative electrode material, and assembled with the positive electrode / electrolyte separator composite sheet to obtain a thermal battery monomer.

[0051] In an argon environment and with an external heat source temperature of 500°C, the thermal battery discharge current density was measured to be 0.3A / cm 2 , the discharge curve test results when the cut-off voltage is 0.3V are as follows Figure 5As shown by the solid line in the middle, its discharge specific capacity can reach 385mAh / g, the discharge voltage platform is stable, the maximum voltage during the discharge process can reach 2.25V, and the corresponding maximum specific power is 10.14kW / Kg.

[0052] The titanium nitride powder additive in this embodiment is replaced with magnesium oxide powder of the same mass, and the composite positive electrode material is prepared by the same method as in this embodiment and then assembled into a thermal battery cell as a comparison sample of this embodiment. The discharge curve is tested under the same conditions. The test results are as follows: Figure 5 As shown by the middle dotted line, the discharge voltage platform is stable, the maximum voltage during the discharge process reaches 2.19V, and the corresponding maximum specific power is 9.88kW / Kg. Compared with the composite positive electrode material of this embodiment, the composite positive electrode material has a smaller specific power.

[0053] Example 4

[0054] A high-performance thermal battery composite positive electrode material, the preparation method is as follows:

[0055] 1) The dried magnesium oxide and titanium nitride are fully ball-milled in a mass ratio of 5:5 to obtain an additive powder, and LiCl powder, LiF powder, and LiBr powder are placed in a ball mill in an argon atmosphere in a mass ratio of 22:9.6:68.4, and then the ball-milled mixed powder is pre-melted to obtain LiCl-LiF-LiBr molten salt, and then the molten salt is crushed and ball-milled at a speed of 300-400 rpm for 2 hours to obtain a molten salt electrolyte powder, and finally the molten salt electrolyte powder and the additive powder are weighed in a mass ratio of 1:1, and ball-milled for 1 hour to obtain a composite molten salt electrolyte powder;

[0056] 2) NiCl2·6H2O was placed in a vacuum drying oven and vacuum dried at 200°C for 4 hours. After natural cooling, it was ground evenly and transferred to a tube furnace. The temperature was increased from room temperature to 300°C at a heating rate of 10°C / min and kept for 2 hours, and then increased to 600°C and kept for 4 hours to obtain pure NiCl2 powder;

[0057] 3) The composite molten salt electrolyte powder prepared in step 1) and the NiCl2 powder prepared in step 2) are weighed in a mass ratio of NiCl2 powder: composite molten salt electrolyte powder = 7:3, and then ball-milled to obtain a composite positive electrode material.

[0058] Under argon atmosphere, the composite positive electrode powder (0.2 g) obtained in this example was spread in a stainless steel tableting mold with an inner diameter of 17.5 mm, and then 0.3 g of electrolyte separator powder (LiCl-LiF-LiBr-MgO) was spread on it, and the tablet was pressed at a pressure of 5 MPa, and the pressure was maintained for 1 min. The positive electrode / electrolyte separator composite sheet was obtained by demolding. A lithium-boron alloy sheet was further selected as the negative electrode material, and assembled with the positive electrode / electrolyte separator composite sheet to obtain a thermal battery monomer.

[0059] In an argon environment and with an external heat source temperature of 500°C, the thermal battery discharge current density was measured to be 0.1A / cm 2 When the cut-off voltage is 0.3V, the test results are as follows: Figure 6 As shown, its discharge specific capacity can reach 275.71mAh / g, the discharge voltage platform is stable, the maximum voltage during the discharge process can reach 2.48V, and the corresponding maximum specific power is 4.26kW / Kg.

Claims

1. A high-performance thermal battery composite positive electrode material, characterized in that: The high-performance thermal battery composite positive electrode material is obtained by mixing nickel chloride and composite molten salt electrolyte powder by ball milling, wherein the mass fraction of nickel chloride is 60-90%, and the mass fraction of composite molten salt electrolyte powder is 10-40%; The composite molten salt electrolyte powder is obtained by mixing molten salt electrolyte powder and additives and ball milling for 1 to 2 hours, wherein the mass ratio of the molten salt electrolyte powder to the additive is 1:1; The molten salt electrolyte powder is one of LiCl-KCl molten salt powder, LiCl-LiF-LiBr molten salt powder, and LiF-LiBr-KBr molten salt powder; The additive is a mixed powder obtained by mixing and ball-milling magnesium oxide and titanium nitride, wherein the mass ratio of magnesium oxide to titanium nitride is one of 0:10, 3:7, 5:5 and 7:

3.

2. The high-performance thermal battery composite positive electrode material according to claim 1, characterized in that: The preparation method of nickel chloride is as follows: NiCl2·6H2O is placed in a vacuum drying oven, dried at 200°C for 2-4 hours, ground after cooling, and then transferred to a tube furnace, heated from room temperature to 250-350°C at a heating rate of 10°C / min, kept warm for 2-4 hours, and then heated to 500-700°C, kept warm for 4-6 hours, to obtain pure phase NiCl2 powder.

3. A method for preparing a high-performance thermal battery composite positive electrode material according to claim 1 or 2, characterized in that: The specific steps are as follows: 1) Weigh nickel chloride and composite molten salt electrolyte powder in proportion and set aside; 2) The nickel chloride and composite molten salt electrolyte powders weighed in step 1) are mixed and ball-milled to obtain a high-performance thermal battery composite positive electrode material.

4. The method for preparing a high-performance thermal battery composite positive electrode material according to claim 3, characterized in that: Step 2) ball milling process conditions are: ball milling speed 200-350 rpm, ball milling time 1-2 h.

5. Use of the high-performance thermal battery composite positive electrode material according to claim 1 or 2 as a positive electrode material in the field of thermal batteries.

Citation Information

Patent Citations

  • A lithium thermal battery with high voltage

    CN109167080A

  • Thermal battery nickel dichloride positive electrode film material and preparation method thereof

    CN112234162A

  • Cell

    CN1311902A